Sugars and Polyols of Natural Origin as Carriers for Solubility and Dissolution Enhancement - Madan Sai Poka; Marnus Milne; Anita Wessels; Marique Aucamp (MDPI AG, 2023)
Crystalline carriers such as dextrose, sucrose, galactose, mannitol, sorbitol, and isomalt have been reported to increase the solubility, and dissolution rates of poorly soluble drugs when employed as carriers in solid dispersions (SDs). However, synthetic polymers dominate the preparation of drugs: excipient SDs have been created in recent years, but these polymer-based SDs exhibit the major drawback of recrystallisation upon storage. Also, the use of high-molecular-weight polymers with increased chain lengths brings forth problems such as increased viscosity and unnecessary bulkiness in the resulting dosage form. An ideal SD carrier should be hydrophilic, non-hygroscopic, have high hydrogen-bonding propensity, have a high glass transition temperature (Tg), and be safe to use. This review discusses sugars and polyols as suitable carriers for SDs, as they possess several ideal characteristics. Recently, the use of low-molecular-weight excipients has gained much interest in developing SDs. However, there are limited options available for safe, low molecular excipients, which opens the door again for sugars and polyols. The major points of this review focus on the successes and failures of employing sugars and polyols in the preparation of SDs in the past, recent advances, and potential future applications for the solubility enhancement of poorly water-soluble drugs.